PENGARUH EXPERIENTAL MARKETING DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN RESTORAN KALI UCENG KECAMATAN KASEMBON - Trilestari, Ika; Meilina, Restin; Bhirawa, Sigit Wisnu Setya (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2024)
This study aims to analyze the influence of experiential marketing and store atmosphere on purchase decisions at Kali Uceng Restaurant. The research uses a quantitative method with a causal approach, involving 60 respondents who have previously shopped at the restaurant. Data was collected through questionnaires. Thefindings show that: 1) experiential marketing significantly influences purchase decisions (sig. value 0.005), 2) store atmosphere also has a significant impact (sig. value 0.030), and 3) both variables simultaneously have a significant effect (sig. value 0.000) on purchase decisions. Kali Uceng Restaurant is advised to enhance its experiential marketing, as it has the largest impact, and improve its store atmosphere to further influence purchasing decisions. Future research is recommended to include additional variables and different research models to strengthen the findings.